The Effect of Acute Endurance Exercise on Plasma Myostastin in Healthy Elderly Men - Meysam Gholamali; Maryam Nourshahi; Mehdi Hedayati (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives We aimed to investigate the effect of acute endurance exercise on the amount of Myostatin, as most important protein, involved in sarcopenia in healthy elderly men. Methods & Materials 11 healthy elderly men (mean age=68±2.1 years, height=177±1.3 cm, weight=79±1.5) volunteered to participate in this study. At first, the subject’s descriptive and physiological measurements have been done. 72 hours after the determination of maximal oxygen consumption (VO2max), subjects performed acute endurance exercise via 70% VO2max. 3 blood samples were collected from antecubital vein before, immediately and 4 hours after the exercise, for assessing the effect of endurance exercise on plasma Myostatin. Plasma Myostatin was measured by ELISA method. One-way ANOVA used for statistical analyses. Significance level was set at P≤0.05. Results The results of this study showed that at immediately and 4 hours after the exercise the plasma Myostatin decreased to 45.47% (P=0.002) and 53.53% (P=0.001), respectively. These decrements were significant. Also, plasma Myostatin at 4 hours after the exercise decreased non-significantly (15.87%) compared with immediately after the exercise.    Conclusion Plasma Myostatin decreased significantly in the response to endurance exercise, in healthy elderly men. Presumably, according to the results of this study, prescription of endurance exercise may decrease Myostatin and subsequently sarcopenia in elderly people.